A Systematic Review on the Integration of Mobile Applications in Chemistry Education: Trends and Effectiveness - Ayu Ashari; Munawwarah Munawwarah (Jurnal Pendidikan Ilmu Pengetahuan Alam (JP-IPA), 2026)
Chemistry education is often perceived as difficult by students due to the abstract and complex nature of its concepts, especially in linking macroscopic phenomena to submicroscopic levels. This study aims to identify the trends and effectiveness of the integration of mobile applications in chemistry education and their impact on student motivation and understanding. The method used is a Systematic Literature Review (SLR) with the PRISMA protocol. From an initial search of 193 articles on Google Scholar and Scopus from 2020 to 2026, 13 articles that met the inclusion criteria were selected for further analysis. The results show that the use of technologies such as Augmented reality (AR), Virtual laboratories, Simulations, and Game-based learning significantly enhances student engagement and facilitates 3D molecular structure visualization. However, technical challenges such as device limitations, smartphone sensor accuracy, and the still-limited coverage of topics remain major barriers. This study concludes that mobile applications are an effective complement to traditional teaching methods in creating a more inclusive and interactive learning environment.